Prediction of Ultimate Strength of Steel-Concrete Composite Beams with Metal Deck Slab Using Artificial Neural Network - Mtasher, Rana Auda (Basrah Journal for Engineering Sciences, 2010)
This paper explores the potential of using artificial neural networks to predict the ultimate moment capacity of steel-concrete composite beams with metal deck slabs. Basic information on artificial neural networks and parameters suitable for the analysis of experimental results are given. A multilayer backpropagation neural network is used for training and testing the experimental data. A comparison study between the experimental values and two models (neural network and AJSC models) is also carried out. It was found that 1he neural network model provides better results. The proposed neural network is also used to explore the effect of the various parameters on the behavior of beams.